Mediating effects of customer perceived value on relationship among service quality, customer experience and customer satisfaction of E-banking services in Bangladesh - Bashir, Md Abdul (2022)
The banking sector unquestionably plays a critical role in any country's economic development and social growth in terms of wealth generation, which positively affects Gross Domestic Product (GDP). Technological advances have made remote sales and administration of financial services and products possible for years. The banking structure and procedures have been modified and revised daily since its inception. It is acknowledged that the banking industry is the one that is primarily affected by the internet and developments in information communication technology (ICT). Traditional financial services providers and new entrants are exploring e-possibilities. E-banking makes accessing bank accounts online easy, quick, and safe. Information technology is cost-efficient, easy-to-maintain, fast, effective, and competitive. Previous research found that e-banking clients are more responsive to behavioural variables than internal considerations. Behavioural characteristics and e-banking technologies affect customers' online banking experiences and satisfaction. Thus, e-banking adoption directly affects customers’ satisfaction with service delivery based on behavioural characteristics. This research examines how customers’ perceived value affects e-banking service quality, customers’ experience, and customers’ satisfaction in Bangladesh. 323 E-Banking clients were surveyed using a standardised questionnaire and random selection. A five point "Likert-Type Scale" has been adopted to measure the direct and indirect effects including independent, dependent, and mediating variables. Five hypotheses were derived from the technology acceptance model (TAM's) assumptions. Descriptive Analysis, Zero Order Karl Pearson's correlation analysis and CB-SEM path analysis were utilised to derive a conclusion. The research found that service quality and customers’ experience affect e-banking in Bangladesh. Perceived value mediates the links between service quality, customers’ experience, and customer satisfaction. Theoretically, these research results support the assumptions of TAM. This research will help the banking authorities focus more on service quality to improve customer satisfaction by recommending methods to make e-banking smoother, more effective, and safer. This study is purely quantitative in nature; in future research should be qualitative or mixed to get more accurate scenario regarding this issue. Out of eight divisions, only four divisions have been considered in this study, thus it is suggested to add more divisions to generalize the findings.